Pengaruh Geometri dan Polarisasi Cahaya terhadap Resonansi Plasmon Nanopartikel Ellipsoid Core-Shell SiO₂@Ag dan SiO₂@Au - Noni Novianti; Abi Syaibah; Ikhwan Fikri Maulidan; Mulda Muldarisnur (Jurnal Fisika Unand, 2025)
This study reports the optical behaviors of SiO₂@Ag and SiO₂@Au core-shell ellipsoidal nanoparticles in terms of polarization of light and geometrical parameter changes. The particles showed two strong modes of resonances, longitudinal and transversal, which could be controlled by rotating the polarization of incident light by 90° and thus could find applications as sensor and optical switch devices. While the resonant wavelength is independent of polarization direction, while maximum extinction values indicate pronounced changes. SiO₂@Ag nanoparticle exhibit higher maximum extinction as well as the peak of resonance at a shorter wavelength than SiO₂@Au. Furthermore, an increase in the ratio of core diameter to shell induces a blue-shift and increasing extinction value. The overall particle size has no influence on the location of the peak of the resonance but increases the extinction intensity. The larger ratio of short axis to long axis also brings about blue-shift in longitudinal resonances. The finding demonstrates that core-shell structure control and morphology control can be used to engineer nanoparticle optical performance in diverse nanophotonic applications.